2021
DOI: 10.3390/molecules26020435
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione in Protein Redox Modulation through S-Glutathionylation and S-Nitrosylation

Abstract: S-glutathionylation and S-nitrosylation are reversible post-translational modifications on the cysteine thiol groups of proteins, which occur in cells under physiological conditions and oxidative/nitrosative stress both spontaneously and enzymatically. They are important for the regulation of the functional activity of proteins and intracellular processes. Connecting link and “switch” functions between S-glutathionylation and S-nitrosylation may be performed by GSNO, the generation of which depends on the GSH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 156 publications
(177 reference statements)
2
39
0
3
Order By: Relevance
“…If for ROS overproduction mitochondrial malfunctioning is certainly imputed as the main cause [ 50 ], in the case of excessive RNS formation the main origin is linked to overexpression of inducible nitric oxide synthase (iNOS) with a consequent high rate of nitric oxide generation [ 51 ], often mediated by (neuro)inflammatory processes [ 52 , 53 ]. In preclinical and clinical studies of ALS, clear evidence of ROS and RNS-mediated damages have previously been shown [ 54 , 55 , 56 , 57 ] accompanied by a decrease in brain and muscle concentrations of reduced glutathione [ 58 , 59 ], i.e., one of the most important intracellular water-soluble antioxidant and scavenger of excessive formation of nitric oxide and RNS [ 60 ]. In the cohort of patients with ALS, we found that both MDA (quantified by direct HPLC method with no derivatization) and the sum of nitrite + nitrate were, before treatment, significantly higher than the values recorded in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…If for ROS overproduction mitochondrial malfunctioning is certainly imputed as the main cause [ 50 ], in the case of excessive RNS formation the main origin is linked to overexpression of inducible nitric oxide synthase (iNOS) with a consequent high rate of nitric oxide generation [ 51 ], often mediated by (neuro)inflammatory processes [ 52 , 53 ]. In preclinical and clinical studies of ALS, clear evidence of ROS and RNS-mediated damages have previously been shown [ 54 , 55 , 56 , 57 ] accompanied by a decrease in brain and muscle concentrations of reduced glutathione [ 58 , 59 ], i.e., one of the most important intracellular water-soluble antioxidant and scavenger of excessive formation of nitric oxide and RNS [ 60 ]. In the cohort of patients with ALS, we found that both MDA (quantified by direct HPLC method with no derivatization) and the sum of nitrite + nitrate were, before treatment, significantly higher than the values recorded in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Of the amino acid side chains, cysteine and tyrosine are most susceptible to oxidation by ROS and RNS. The free thiol (or thiolate) of cysteine residues can react with NO-derived oxidants or nitrosonium donors such as GSNO ( Smith and Marletta, 2012 ; Wynia-Smith and Smith, 2017 ; Massa et al, 2021 ), peroxides such as H 2 O 2 ( Yang et al, 2016 ) or ONOO – ( Alvarez and Radi, 2003 ), and glutathionylating agents such as glutathione disulfide (GSSG) or H 2 O 2 /glutathione ( Kalinina and Novichkova, 2021 ). Overall, sirtuins are differentially sensitive to oxidative post-translational modification with distinct sets of oxidants.…”
Section: Protein Oxidative Post-translational Modificationsmentioning
confidence: 99%
“…Formation of nitrosothiols or sulfenic acids on a protein or GSH can precede glutathionylation, whereby GSH reacts with sulfenylated or nitrosated cysteines to yield glutathionylated protein and H 2 O or HNO, respectively. For example, in the presence of H 2 O 2 and reduced glutathione (GSH), H 2 O 2 can react with a protein cysteine thiol to form a transient sulfenic acid, followed by nucleophilic attack of the sulfenic acid by the GSH thiol resulting in glutathionylation ( Kalinina and Novichkova, 2021 ). Alternatively, in a thiol-disulfide exchange reaction, GSSG can react with a cysteine thiol to yield a glutathionylated cysteine and GSH.…”
Section: Protein Oxidative Post-translational Modificationsmentioning
confidence: 99%
“…GSH is also used as a substrate in reactions catalyzed by GPXs in the ascorbate-glutathione cycle (Vanderauwera et al, 2011;Tuzet et al, 2019). Moreover, GSSG reacts non-enzymatically with protein thiol groups creating protein-SSG mixed disulfides (Kalinina and Novichkova, 2021). An appropriate GSH/GSSG ratio is crucial for cellular redox homeostasis and regulates cell metabolism including the accumulation and transport of Cys, and participates in the regulation of gene expression, DNA and protein synthesis, regulation of cell cycle, cell differentiation, and PCD (Foyer et al, 2001;Foyer and Noctor, 2005;Maughan and Foyer, 2006;Szalai et al, 2009;Queval and Foyer, 2012;Deponte, 2013;Schnaubelt et al, 2015).…”
Section: Cysteine-rich Tripeptide (Glutathione)mentioning
confidence: 99%